2012
DOI: 10.1155/2012/716404
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Metformin in the Management of NAFLD

Abstract: Nonalcoholic fatty liver disease (NAFLD) is the most common liver disorder worldwide. Its prevalence ranges 10–24% in the general population, reaching 60–95% and 28–55% in obese and diabetic patients, respectively. Although the etiology of NAFLD is still unclear, several lines of evidences have indicated a pathogenetic role of insulin resistance in this disorder. This concept has stimulated several clinical studies where antidiabetic drugs, such as insulin sensitizers including metformin, have been evaluated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
127
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(133 citation statements)
references
References 111 publications
(151 reference statements)
5
127
1
Order By: Relevance
“…While the prevalence of NAFLD ranges 10-24% in the general population, it may reach 60-95% and 28-55% in severely obese and diabetic patients, respectively [8] . In this context, it has be hypothesized that NAFLD may be considered as a new target for T2DM prevention and treatment [9] .…”
Section: Introductionmentioning
confidence: 99%
“…While the prevalence of NAFLD ranges 10-24% in the general population, it may reach 60-95% and 28-55% in severely obese and diabetic patients, respectively [8] . In this context, it has be hypothesized that NAFLD may be considered as a new target for T2DM prevention and treatment [9] .…”
Section: Introductionmentioning
confidence: 99%
“…The authors explained the strict inclusion criteria with the histological definition of NAFLD or NASH, while only three RCTs were included as barriers to the meta-analysis with regards to the effect of metformin on NAFLD. However, several studies, including more recent RCT data, and an additional review have shown that metformin may improve metabolic variables in NAFLD patients, especially in patients meeting the diagnostic criteria of metabolic syndrome (18). Therefore, the aim of this systematic review and meta-analysis was to further assess the beneficial and harmful effects of metformin on NAFLD.…”
Section: Metformin In Non-alcoholic Fatty Liver Diseasementioning
confidence: 99%
“…Especially no increased risk of lactic acidosis has been reported. Metformin may potentially exert beneficial effects in patients with NAFLD, although the evidence remains rather scarce [59][60][61].…”
Section: Metformin In Patients With Hepatic Dysfunctionmentioning
confidence: 99%